Species of Entoloma (Entolomataceae) with cuboidal basidiospores from Brazil - Karstedt, Fernanda; Bergemann, Sarah E.; Gates, Genevieve; Ratkowsky, David; Cunha, Kelmer Martins; Capelari, Marina (Phytotaxa, 2024)
Fifteen new species of Entolomataceae in Entoloma subg. Cubospora characterized by having cuboidal basidiospores are presented in this paper. We provide new morphological information, including clarified and expanded morphological descriptions, molecular work and SEM photos (when possible) on a further 12 species already known. The specimens came from two differing vegetation types in Brazil: the Amazon Rainforest and the Atlantic Forest. We provide phylogenetic data, detailed descriptions, comparisons with other similar species and a key to the 27 species. The morphological and molecular data suggest the subclades /Psittacini, /Murrayi, /Acutipallidum, /Dragoluteum, /Cervinum, /Procerum and /Dragonosporum.